Profil Model Pendidikan Keterampilan dalam Sistem Pendidikan Terpadu Pesantren sebagai Proses Pemberdayaan Santri - H. Engking Soewarman Hasan (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
The aim of this study was to reveal the developmental aspects of a model of vocational education as an empowering process. The subjects were santri of Pondok Pesantren Darussalam, Ciamis, West Java. Data were collected by participant observation, inteview, and document analysis. The technique of data analysis was qualitative analysis. It was found out that, in management aspect, a guide for vocational education was successfully made. The objectives of each kind of vocational education and the application of learning strategies were successfully arranged. In the evaluation and development aspects, the varied evaluation techniques, the systematized steps of evaluation, a set of evaluation formats, the criteria of the success of the program, and the formulation of follow-up activities were successfully constructed.